Transmission spectra of single ring coupled-waveguide resonator configuration by finite difference time domain method - Haryana bin Mohd Hairi; Saktioto Saktioto; Romi Fadli Syahputra; Okfalisa Okfalisa; Sofia Anita (Universitas Ahmad Dahlan, 2020)
Development of optical waveguide resonators have greatly expanded and continues to grow since they have kinds potential applications such as wavelength filtering, switching, coupling and multiplexing. One of resonators, coupled waveguides, ring resonators are designed and operated using various coupling configurations. Ring resonators can be particularly used as wavelength filter if the wavelength can fit a whole multiple time in the circumference of the ring. This article proposes to investigate the transmission spectra from the power source and amplify it in linearized ring resonator configurations and varies the input amplitude on five different wavelengths. With finite difference time domain method, the geometry and power source are simulated to obtain the better result and configuration. The results show the intensity phenomena of filtering in optical circuit.